Archipelagic Economies : Spatial Economic Development in the Pacific - Utz, Robert J. (World Bank, Washington, DC, 2021)
This study explores the far-reaching economic consequences emerging from the archipelagic nature of most Pacific Island countries (PICs). The dispersion of populations across thousands of miles of ocean and hundreds of islands magnifies the economic disadvantages arising from the remoteness and small size that characterize the PICs as a whole. At the same time, population dispersion creates extraordinary challenges related to public service delivery, connectivity, migration and urbanization, and the equity and inclusiveness of economic development. This study focuses on these challenges in pursuit of two main objectives: deepening the understanding of socio-economic conditions on the PICs’ outer islands and the drivers of migration from outer islands to main islands; and reviewing the policy and investment options for fostering the socio-economic development of outer islands populations. This overview summarizes the main findings in five parts. First, the authors present the objectives and outline of the full report. This is followed by a section which explains how the PICs’ external and internal geography are key determinants of socio-economic development outcomes and spatial inequalities. The third part presents data on spatial inequality with respect to a range of socio-economic indicators, public services, connectivity, and migration. In the fourth part, the authors discuss interactions between geographic dispersion and key political economy issues that shape spatial economic policy decisions and outcomes. The report concludes with a summary of policy options for dealing with the development challenges arising from geographic dispersion.